Analysis of propagation delay and repeater insertion in single-walled carbon nanotube bundle interconnects. (August 2016) - Lu, Qijun; Zhu, Zhangming; Yang, Yintang; Ding, Ruixue
Abstract: A new closed-form expression of 50% propagation delay for distributed RLC interconnects is proposed using the multivariable curve fitting method, with a maximum error of 4% with respect to SPICE results. Then accurate closed-form solutions for the optimum repeater number and size to minimize the propagation delay are further derived. The performance of single-walled carbon nanotube (SWCNT) bundle interconnects is evaluated using the proposed models in the intermediate and global levels at the 22- and 32-nm technology nodes, and compared against traditional Cu interconnects. It is shown that the performance of SWCNT bundle interconnects in propagation delay can outperform Cu interconnects, and the improvement will be enhanced with technology scaling and wire length increasing. On the other hand, the propagation delay of SWCNT bundle interconnects is super-linearly dependent on the wire length similar to Cu interconnects, indicating that the method of repeater insertion to reduce the propagation delay can also apply to SWCNT bundle interconnects. The results shown that repeater insertion can really reduce the propagation delay of SWCNT bundle interconnects effectively, and the optimum repeater number is much smaller than that of Cu interconnects.